Two frequent polymorphisms of angiotensinogen and their association with multiple sclerosis progression rate - Hladikova, Magdalena; Vašků, Anna; Stourač, Pavel; Benešová, Yvonne; Bednařík, Josef (Journal of the neurological sciences, 2011)
A total of 195 patients with multiple sclerosis (MS) and 126 controls were investigated for angiotensinogen/(-6)A/G, M235T/and angiotensin converting enzyme I/D gene polymorphisms to test their association with MS susceptibility and/or disease progression using Global Multiple Sclerosis Severity Score (MSSS). We demonstrated a significant association of M235T polymorphism with MSSS. The MM homozygotes had the lowest (3.8), heterozygotes MT higher (5.2) and homozygotes TT the highest (5.4) mean MSSS values (P=0.02). For polymorphisms (-6)A/G of ATG, only a trend was observed (P=0.06), where the homozygotes GG carried lower MSSS values than heterozygotes and homozygotes AA. No significant association with susceptibility was observed. For ACE I/D polymorphism, neither significant differences in the genotype-phenotype study nor in the case-control study were observed.
Keywords: dospělí; heterozygot; Genotype; Female; angiotensin konvertující enzym; Adult; homozygot; ženské pohlaví; angiotensinogen; lidé; Heterozygote; Multiple Sclerosis; renin-angiotensin systém; genotyp; Renin-Angiotensin System; roztroušená skleróza; genetická predispozice k nemoci; studie případů a kontrol; Genetic Predisposition to Disease; Homozygote; Genetic Variation; Peptidyl-Dipeptidase A; Male; progrese nemoci; Case-Control Studies; Disease Progression; polymorfismus genetický; alely; Alleles; mužské pohlaví; Angiotensinogen; genetická variace; Polymorphism, Genetic; Humans